(untitled) (Journal of Asian Development Studies, 2024)
This study explores speech anxiety in students learning English as an additional language (EAL) in a university setting. Addressing classroom speech anxiety among university students is paramount for fostering supportive learning environments and ensuring academic success (Horwitz, 2001). Reducing classroom speech anxiety boosts students’ confidence and persuasive communication skills, which are crucial for professional success (McCroskey, 1982). This research examined the many elements that influence classroom speaking anxiety in students at the University of Education Lahore. The theoretical foundation of this research was the Foreign Language Classroom Anxiety Scale (FLCAS) developed by Horwitz et al. (1986). The questionnaire consisted of 25 items and was delivered to the Bachelor of Science (BS) English department students. One hundred and three students responded to the questionnaire. Data was analyzed quantitatively using the Statistical Package for the Social Sciences (SPSS) version 16, which was launched in 2007. Results show that there is significant speech anxiety in students based on their demographic background. The analysis of an open-ended question included in the questionnaire reveals that psychologically, students think they have less competence than their fellow students, followed by other psychological factors like fear of judgment and peer comparison. It is recommended that EAL instructors should implement strategies aimed at lowering students’ anxiety levels so they can perform to the best of their abilities.